The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1152/japplphysiol.90461.2008
|View full text |Cite
|
Sign up to set email alerts
|

Neuromechanical control of the isolated upper airway of mice

Abstract: Liu A, Pichard L, Schneider H, Patil SP, Smith PL, Polotsky V, Schwartz AR. Neuromechanical control of the isolated upper airway of mice. J Appl Physiol 105: 1237-1245, 2008. First published July 24, 2008 doi:10.1152/japplphysiol.90461.2008.-We characterized the passive structural and active neuromuscular control of pharyngeal collapsibility in mice and hypothesized that pharyngeal collapsibility, which is elevated by anatomic loads, is reduced by active neuromuscular responses to airflow obstruction. To addr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 60 publications
1
14
0
1
Order By: Relevance
“…These flow-limited breaths were characterized by a decrease in inspiratory flow, an increase in inspiratory time, an increase in respiratory movement, and negative effort dependence, all of which are consistent with the development of dynamic upper airway obstruction (42). Previous studies have suggested that the most likely site of extrathoracic obstruction in the mouse is the pharynx (4,5,21,36). IFL in a sleeping mouse is a novel, potentially intriguing finding and suggests that this strain might serve as mouse model of OSA.…”
Section: Mouse Polysomnography and Iflsupporting
confidence: 64%
“…These flow-limited breaths were characterized by a decrease in inspiratory flow, an increase in inspiratory time, an increase in respiratory movement, and negative effort dependence, all of which are consistent with the development of dynamic upper airway obstruction (42). Previous studies have suggested that the most likely site of extrathoracic obstruction in the mouse is the pharynx (4,5,21,36). IFL in a sleeping mouse is a novel, potentially intriguing finding and suggests that this strain might serve as mouse model of OSA.…”
Section: Mouse Polysomnography and Iflsupporting
confidence: 64%
“…Obesity also is an important factor affecting upper airway motor tone and airway collapsibility in humans (Schwartz et al, 1991; O'Donnell et al, 2000). Obese rodents, like obese humans, have less negative upper airway critical pressures than their lean controls (Ogasa et al, 2004; O'Donnell et al, 2000) and obese mice exhibit tonic upper airway activation under anesthesia (Liu et al, 2008; Brennick et al, 2009). However, the available evidence suggests that the levels and patterns of lingual EMG across sleep-wake states are similar in obese and lean rats (Sood et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…A major criticism of using MRI and CT in studies is that they are performed during wakefulness, a period during which upper airway muscles are active, and therefore they do not represent the actual behaviour of the upper airway during sleep . To minimize the confounding effect of neuromuscular activation during wakefulness, we explored airway distensibility/collapsibility during the expiratory phase. The size of the upper airway is determined by the balance between airway flow (luminal pressure) and the inward tissue pressure of upper airway tissue (tissue pressure).…”
Section: Discussionmentioning
confidence: 99%
“…Pharyngeal tissue distensibility is an indicator of the ease with which the airway can be deformed (and therefore also an indicator of the ease with which the airway can collapse) and is a measure of a passive property of the tissues. Innate distensibility and collapsibility are difficult to quantify during wakefulness because of confounding input from neuromuscular activation . During the respiratory cycle in the awake state, the upper airway cross section increases maximally in early expiration, decreases to a minimum at end expiration and remains relatively constant during the inspiratory phase (presumably due to the activation of upper airway dilator muscles) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation